2021
DOI: 10.1520/jte20190255
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior and Thermal Conductivity of Graphite–Ethylene Glycol Nanofluid

Abstract: The rheological behavior and thermal conductivity of graphite–ethylene glycol (EG) nanofluid is investigated in this research work. The nanofluid is prepared by two-step method using polyvinylpyrrolidone as surfactant. Volume concentration (vol. %) of 0.2, 0.8, and 2 % graphite-EG nanofluid are prepared by ultrasonicating for 5 h. Initially, the effect of temperature variation from 25°C to 60°C (with a difference of every 2.5°C) on the viscosity of prepared nanofluid for different volume concentrations is stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Recently, carbon-based nanoparticles and two-dimensional nanostructures have captivated ample attention due to their comparatively higher thermal conductivity, greater specific surface area, better compatibility with base fluid, better lubricating property, and ample availability when compared with other nanoparticles [ 25 , 26 ]. A broad number of studies were performed with graphite [ 27 ], carbon nanotubes(CNTs) [ 28 , 29 ], graphene [ 30 ], graphene oxide (GO) [ 31 ], nano diamond [ 32 ], and graphite flake [ 33 ] nanoparticles so far. Yu et al [ 34 ] experimentally measured the thermal conductivity of EG based nanofluid with GO nanosheets where thermal conductivity was noticeably higher by 61% compared to pure EG, while the nanosheet concentration was 5 vol %.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, carbon-based nanoparticles and two-dimensional nanostructures have captivated ample attention due to their comparatively higher thermal conductivity, greater specific surface area, better compatibility with base fluid, better lubricating property, and ample availability when compared with other nanoparticles [ 25 , 26 ]. A broad number of studies were performed with graphite [ 27 ], carbon nanotubes(CNTs) [ 28 , 29 ], graphene [ 30 ], graphene oxide (GO) [ 31 ], nano diamond [ 32 ], and graphite flake [ 33 ] nanoparticles so far. Yu et al [ 34 ] experimentally measured the thermal conductivity of EG based nanofluid with GO nanosheets where thermal conductivity was noticeably higher by 61% compared to pure EG, while the nanosheet concentration was 5 vol %.…”
Section: Introductionmentioning
confidence: 99%
“…This instrument works on the principle of the transient hot wire method (THWM). KD2 Pro is one of the simple and accurate method to measure thermal conductivity and has been used broadly by many researchers [39,[41][42][43][44]. This instrument consists of a battery, microcontroller and a sensor needle.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…Nanoparticles of different sizes have been produced using several methods [37,38]. However, T -S method was widely adopted by the researchers in the preparation of many types of nanofluids [20,35,[39][40][41] due to ease in preparation of predetermined concentration. Graphite nanopowder (Sisco Research Lab (SRL), Maharashtra) with particle size <50 nm was procured to prepare Water -Graphite nanofluids.…”
Section: Nanofluid Preparationmentioning
confidence: 99%
“…From the study, it was observed that 10.29% enhancement in viscosity was found for 2% of weight concentration at 20°C compared with base fluid. Brownian motion and van der Waals forces are the primary contributors 53,54 for the increase in viscosity of nanofluid. Accordingly, for 0.2, 0.5, 1, and 1.5 wt% concentration, the CHTC obtained was 6.43%, 14.25%, 23.61%, and 28.94% greater than that of base fluid respectively.…”
Section: Viscositymentioning
confidence: 99%
“…Nanofluids have distinct heat transfer characteristics compared with base fluids, such as improved thermal conductivity and greater heat transfer coefficients (HTC). [7][8][9][10][11][12] Researchers have reported significant improvement in heat transfer by using fluids dispersed with solid nanoparticles of different materials. [13][14][15][16][17] Studies have been reported using various techniques to investigate the synthesis, evaluation of properties and determination of heat transfer characteristics of nanofluids.…”
Section: Introductionmentioning
confidence: 99%